Impact of Ganoderma boninense Infection on The Abundance of Cellulolytic And Lignolytic Fungi In The Soil of Oil Palm In Pare-Pare Tengah Village, North Labuhanbatu - Hilwa Walida; Fitra Harahap; Andriansyah; Elgi Ferian Saragih (International Journal of Science and Environment (IJSE), 2026)
Basal Stem Rot (BSR), caused by Ganoderma boninense, is the most destructive disease affecting oil palm (Elaeis guineensis) plantations in Southeast Asia, leading to severe yield losses and threatening the sustainability of the industry. Despite extensive studies on the pathogenicity of Ganoderma, its ecological impact on functional fungal communities in oil palm soils remains poorly understood. This study aimed to evaluate the effect of Ganoderma infection on the abundance of total fungi, cellulolytic fungi, and ligninolytic fungi in oil palm plantation soils in Pare-Pare Tengah Village, North Labuhanbatu, North Sumatra, Indonesia. Soil samples were collected from healthy and infected oil palm stands and analyzed using the Total Plate Count (TPC) method to quantify fungal populations. Statistical analysis using paired t-tests and effect size (Cohen’s d) revealed significant differences between healthy and infected soils. Total fungal abundance decreased from 2.91 × 10⁹ CFU g⁻¹ in healthy soils to 2.16 × 10⁹ CFU g⁻¹ in infected soils (Cohen’s d = 19.15). Similarly, cellulolytic fungi declined from 4.74 × 10⁴ CFU g⁻¹ to 2.51 × 10⁴ CFU g⁻¹ (Cohen’s d = 16.28). Unexpectedly, ligninolytic fungi also showed a marked reduction from 2.22 × 10³ CFU g⁻¹ in healthy soils to 2.01 × 10² CFU g⁻¹ in infected soils (Cohen’s d = 59.14). These findings indicate a substantial shift in soil fungal community structure associated with Ganoderma infection, suggesting complex ecological interactions and potential suppression of other lignocellulose degrading fungi. Understanding these microbial dynamics provides important insights for developing more sustainable and ecologically based management strategies for BSR disease in oil palm plantations.